Progress in Cryptology - INDOCRYPT 2012 13th International Conference on Cryptology in India, Kolkata, India, December 9-12, 2012. Proceedings - Galbraith, Steven; Nandi, Mridul; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 12th International Conference on Cryptology in India, INDOCRYPT 2011, held in Chennai, India, in December 2011. The 22 revised full papers presented together with the abstracts of 3 invited talks and 3 tutorials were carefully reviewed and selected from 127 submissions. The papers are organized in topical sections on side-channel attacks, secret-key cryptography, hash functions, pairings, and protocols.
How to Compute on Encrypted Data -- Using the Cloud to Determine Key Strengths -- On the Non-malleability of the Fiat-Shamir Transform -- Another Look at Symmetric Incoherent Optimal Eavesdropping against BB84 -- Leakage Squeezing of Order Two -- Hash Functions and Stream Cipher -- Collision Attack on the Hamsi-256 Compression Function -- Generalized Iterated Hash Fuctions Revisited: New Complexity Bounds for Multicollision Attacks -- A Di_erential Fault Attack on the Grain Family under Reasonable Assumptions -- Faster Chosen-Key Distinguishers on Reduced-Round AES -- High-Speed Parallel Implementations of the Rainbow Method in a Heterogeneous System -- Computing Small Discrete Logarithms Faster -- Embedded Syndrome-Based Hashing -- Compact Hardware Implementations of the Block Ciphers mCrypton, NOEKEON, and SEA -- A New Model of Binary Elliptic Curves -- Symmetric Key Design and Provable Security SipHash: a fast short-input PRF.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Computational complexity; Information Systems; Computer Science; Data Encryption; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems; Systems and Data Security; Discrete Mathematics in Computer Science